Failure Mechanism and Dynamic Response Characteristics of Loess Slopes Under the Effects of Earthquake and Groundwater - Chai, Shaofeng; Wang, Lanmin; Wang, Ping; Pu, Xiaowu; Xu, Shiyang; Guo, Haitao; Wang, Huijuan (Frontiers in Earth Science, 2022)
Combined with earthquakes and simulated ground water, a large-scale shaking table test was applied to study the dynamic response and instability mechanism of the loess slope with a saturated bottom. By examining the accelerations, dynamic pore water pressures, corresponding soil pressure and observed macroscopic failure behaviours of the slope under different shaking intensities, the dynamic response of acceleration and pore water pressure of the loess slope were analysed. According to the time history curve of acceleration with the time history curve of pore water pressure and surrounding soil pressure, we found that the instability failure of slope is firstly due to the continuous vibration that caused the local structure of slope soil to be damaged, forming local saturated soil along with the rise of groundwater table under the shaking. Then the saturated soil liquefied under the action of strong vibration and the liquefied soil projectile slid under the action of a high-intensity earthquake force. Finally, it was seen that the acceleration and the spectral characteristics of the pore water pressure changed sharply with a shift in the predominant frequency in the liquefied locations under high shaking intensity. The significant changes in dynamic pore water pressure mainly occurred in components in the low frequency bands that are lower than 1 Hz. This inferred that the shift in the frequency mainly resulted from the damage in the structure of the loess slope after shaking with high intensity. These results help us better understand the triggering mechanismthe features of the dynamic pore water pressure and failure mechanism of saturated loess slopes caused by the Minxian-Zhangxian earthquake.